Solid waste management practice and environmental awareness level of postgraduate and undergraduate students: Case study of UTM - Hashim, Kamil; Rabe, Noor Suzilawati; Mohamed Osman, Mariana; Zahari, Rustam Khairi (American Scientific Publishers, 2017)
Higher learning institution is important for the development of cities and solid waste management plan need to be outlined by the higher learning institution comprehensively. In order to reduce the solid waste generated by students in tertiary education, a certain level of awareness should be taught through sustainable solid waste management subject and practices. Respondents among the postgraduate and undergraduate students in Universiti Teknologi Malaysia were collected to assess the their perception, awareness and solid waste practices among the majority of the population for an institution which are the students. The data were collected using a structured questionnaire survey with emphasis on solid waste management knowledge and level of environmental awareness. The questionnaires were distributed to 200 students with the end samples being 111 undergraduate and 89 postgraduate students. The selection of the samples was done using simple-random sampling technique with focus to students from the built environment faculty due to their stronger understanding towards environmental issues. The collected data were analyzed using cross-tabulation between level of study and questions regarding solid waste management and level of environmental awareness. The result shows that postgraduate student does has higher level of awareness in comparison with undergraduate students. This shows that higher learning institution can produce a better geared workforce regarding to sustainable development due to higher awareness on environmental issues and better solid waste management practice.